The Relationships among communication competence, professional autonomy and clinical reasoning competence in oncology nurses - Suyeon Noh; Younhee Kang (Wiley, 2024)
Abstract Aims To investigate the relationships among communication competence, professional autonomy and clinical reasoning and to identify the factors that influence clinical reasoning competence in oncology nurses. Design Cross‐sectional descriptive design. Methods Participants included 147 oncology nurses with more than a year of clinical experience in cancer wards. The Global Interpersonal Communication Competence Scale, Schutzenhofer Professional Autonomy Scale and Nurses Clinical Reasoning Scale (NCRS) were used to collect data. Data were analysed using descriptive statistics, independent t‐test, one‐way ANOVA, Pearson correlation analysis and hierarchical multiple regression analysis. Results Communication competence (r = 0.59) and professional autonomy (r = 0.46) showed significant positive relationships with clinical reasoning competence. Clinical experience, communication competence, age and professional autonomy were statistically significant predictors and explained 48.6% of clinical reasoning competence. Conclusions The clinical reasoning competence of oncology nurses increases proportionally with their communication competence and professional autonomy. Therefore, oncology nurses must reinforce their communication competence and professional autonomy to enhance their clinical reasoning competence. Implications for the Profession and/or Patient Care The reinforcement of communication competence and professional autonomy is necessary for oncology nurses to enhance their clinical reasoning competence. In order to improve nurses' communication competence, practical‐focused communication education programmes must be designed and deployed systematically and periodically. In addition, to increase nurses' professional autonomy, it is necessary to expand their clinical experiences through the regular rotation of working units and to make institutional efforts to retain experienced nurses. Reporting Method We have adhered to STROBE checklist. Patient or Public Contribution Participants in the study were recruited online. They were informed of the study's purpose, method and usability and the survey could only be conducted if they consented to participate voluntarily.